Export Expansion May Increase Adult Illness and Injury: A Quasi-Natural Experiment on China's Accession to the World Trade Organization - Chen, Hongwen; Xu, Junbing; Liu, Jianzheng (Frontiers in Public Health, 2022)
Purpose: Exports can boost the economy, but may also cause harms to health through, for example, increased pollution and working hours. Although academic research extensively covers the impact of trade on health, few studies examine the mechanisms through which export expansion affects adult illness or injury within the past 4 weeks (illness/ injury). Method: We utilized China's entry into the World Trade Organization as a quasi-natural experiment to investigate the relationship between export expansion and adult illness/ injury. We explored possible mechanisms and the heterogeneity of these associations. Our methodology was based on analysis of China's Health and Nutrition Survey data, Chinese Customs databases, and China's Statistical Yearbook. Results: Export expansion, induced by China's accession to the WTO, has a significantly positive effect on adult illness/ injury (Average effect (AE): 1.83%; 95% CI: 0.38%- 3.28%). Our results remain robust following a series of robustness tests. Moreover, the effects of export expansion on adult illness/ injury are more pronounced among urban residents (AE: 5.32%; 95% CI: 2.46%- 8.18%), women (AE: 2.68%; 95% CI: 0.57%- 4.80%), and higher-income groups (AE: 5.90%; 95% CI: 2.53%- 9.27%). Conclusions: We find a statistically significant and positive effect of export expansion on adult illness/ injury.